Quasi-distributed temperature sensing with large-scale draw tower gratings - Härteis, Lisa-Sophie; Renner, Esther; Scheffter, Kilian; Schmauß, Bernhard (Optics InfoBase Conference Papers, 2021)
Large-scale draw tower gratings (DTG) are interrogated using incoherent optical frequency domain reflectometry (iOFDR) w ith h omodyne f requency conversion. We successfully demonstrate quasi-distributed temperature sensing with a total number of N = 500 DTGs.
CRIS-Team Scopus Importer:2021-12-17